2014
DOI: 10.2527/jas.2014-7855
|View full text |Cite
|
Sign up to set email alerts
|

Expression of genes involved in lipid metabolism in the muscle of beef cattle fed soybean or rumen-protected fat, with or without monensin supplementation1

Abstract: Degree of unsaturation of fatty acids, which is influenced by lipid source and level of metabolism in the rumen, is a major determinant in how dietary lipids affect genes that regulate beef marbling. A total of 28 Red Norte bulls with an initial live weight of 361±32 kg (P>0.05) were used in a completely randomized experimental design to analyze the expression of genes that are involved in lipid metabolism in the longissimus dorsi (LD) when diets contained soybean grain or rumen-protected fat, with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 50 publications
1
19
1
Order By: Relevance
“…Furthermore, Herdmann et al (2010) reported that animals fed greater n-3 PUFA content on the diet have less SCD1 expression and thus, less CLA c9,t11-C18:2 and oleic acid on muscle. Ladeira et al (2014) also demonstrated an increase of CLA concentration in the muscle of animals fed soybean compared with those fed rumen-protected fat, and this result may be due to the greater gene expression of SCD1 in the muscle (Oliveira et al, 2014).…”
Section: Gene Expression and Fatty Acid Profilementioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, Herdmann et al (2010) reported that animals fed greater n-3 PUFA content on the diet have less SCD1 expression and thus, less CLA c9,t11-C18:2 and oleic acid on muscle. Ladeira et al (2014) also demonstrated an increase of CLA concentration in the muscle of animals fed soybean compared with those fed rumen-protected fat, and this result may be due to the greater gene expression of SCD1 in the muscle (Oliveira et al, 2014).…”
Section: Gene Expression and Fatty Acid Profilementioning
confidence: 89%
“…Chorner et al (2016) also reported that α-linolenic acid supplementation may result in increased intramuscular lipid content and whole body fat due to the greater rate of lipid transport (FATP and FAT/CD36). In a study of Oliveira et al (2014), the greater C18 fatty acid content in a soybean diet was responsible for greater expression of LPL and FABP4. Therefore, fatty acid profile of the diet may change the expression of membrane transporters, increasing fatty acid uptake.…”
Section: Marblingmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, there is a wide interest in manipulating the chemical composition of meat, through the regulation of its biosynthesis. For better understanding of the effects of nutrition on lipid metabolism and consequently on the quality of meat, recent research has made association between gene expression and nutrition area known as nutrigenomics [20][21][22][23].…”
Section: Literature Review 21 Fat Depositionmentioning
confidence: 99%
“…The authors speculated that the lack of effect of the whole shelled corn diet on marbling was caused by the lower level of SREBF1, since this diet reduced the pH in the rumen and increased the contents of linoleic acid (c9, c12-C18:2). The study of Oliveira et al (2014), where cattle received soybean supplementation, found that the expression of the genes involved in lipid metabolism-such as PPARA, SCD, ACACA, FABP4, lipoprotein lipase (LPL), and glutathione peroxidase (GPX1)-was altered in muscle tissue. On the other hand, alpha-amylase enzyme is often added to beef cattle diets to improve animal performance through improving starch fermentation.…”
Section: Beef Ruminants Postnatal Feeding: Starch Sourcementioning
confidence: 99%